Rejection of the Covid-19 Vaccination in Community Sidourip Village-Beringin District - Nanda Novziransyah; Budi Kurniawan; Mayasari Rahmadhani; Ira Aini Dania; Dewi Pangestuti; Maimunah R. (Qubahan Academic Journal)
: Covid-19 is currently a global concern, with the number of cases increasing daily. Indonesia has the highest rate of confirmed cases in Southeast Asia. The Covid-19 vaccine is one of the government's breakthroughs in the control and management of Covid-19. The aim of Covid-19 vaccination is to reduce spread, morbidity and mortality, achieve immunity and protect the public. However, there are still many groups of people who refuse to be vaccinated. The main objective is to determine the factors associated with community refusal of Covid-19 vaccination in Sidourip village, Beringin district in 2021. Methods are observational-analytical studies with cross-sectional design. Sample size was determined using a convenience sampling method with a sample of 83 people. Relationship between age and community refusal of Covid-19 vaccine p value = 0.003 (p≤0.05). Relationship between work and community refusal of Covid-19 vaccine p value = 0.007 (p≤0.05). Relationship between level of education and community refusal of Covid-19 vaccine p value = 0.000 (p≤0.05). The conclusion is that there is a relationship between age, occupational status and level of knowledge with community rejection of Covid-19 vaccine in Sidourip village, Beringin district in 2021.